2019
DOI: 10.1002/jlb.mr0318-126r
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical regulation of macrophages in health and disease

Abstract: Macrophages perform critical functions for homeostasis and immune defense in tissues throughout the body. These innate immune cells are capable of recognizing and clearing dead cells and pathogens, and orchestrating inflammatory and healing processes that occur in response to injury. In addition, macrophages are involved in the progression of many inflammatory diseases including cardiovascular disease, fibrosis, and cancer. Although it has long been known that macrophages respond dynamically to biochemical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 194 publications
(370 reference statements)
1
98
0
Order By: Relevance
“…To be specific, many reports have demonstrated that the biophysical clues such as the surface topography which the macrophages grow on is critical for polarization regulation. [4][5][6] Our previous studies also indicate that the micro/nano topography of TiO 2 nanotubular surface with ~30 nm diameter is able to induce M2 polarization and consequently influence the osseointegration in vivo. 7,8 This phenomenon has not only provided a more convenient and safe way to induce M2 polarization, but has also led to the concept of "osteoimmunity" during the designation of bone implant.…”
Section: Introductionmentioning
confidence: 81%
“…To be specific, many reports have demonstrated that the biophysical clues such as the surface topography which the macrophages grow on is critical for polarization regulation. [4][5][6] Our previous studies also indicate that the micro/nano topography of TiO 2 nanotubular surface with ~30 nm diameter is able to induce M2 polarization and consequently influence the osseointegration in vivo. 7,8 This phenomenon has not only provided a more convenient and safe way to induce M2 polarization, but has also led to the concept of "osteoimmunity" during the designation of bone implant.…”
Section: Introductionmentioning
confidence: 81%
“…Macrophages fill a crucial role in the host defense to clear pathogens and maintain tissue homeostasis, which are evidently regulated by both biochemical and biomechanical cues [for reviews, see Refs. 8 , 9 , 10 , 11 ]. Firstly, like other immune cells, monocytes need to migrate to inflamed sites.…”
Section: Mechano-regulation Of Innate Immunitymentioning
confidence: 99%
“…Mimicking mechanical cues that are experienced by macrophages in the lung, cyclical hydrostatic pressure initiates an inflammatory response via the mechanically activated ion channel Piezo1 [ 5 •• , for additional stretch effects on macrophages, see Ref. 10 ].…”
Section: Mechano-regulation Of Innate Immunitymentioning
confidence: 99%
“…Similarly, macrophages have been extensively reported to be sensitive to ECM composition, stiffness, and topographical and adhesive cues [97]. On diverse 2D ECM-coated surfaces, macrophages adopt varied morphologies, while also demonstrating divergent potential for polarization [98].…”
Section: Tumor-associated Matrix Cues Contribute To Immune Cell Activmentioning
confidence: 99%